'STEMI–like' acute pulmonary embolism, an unusual presentation. (20th November 2014) - Abdalla, Abuelmagd; Kelly, Frank
Abstract : We present the case of a 65-year-old man with an atypical presentation of pulmonary embolism (PE) as ST elevation myocardial infarction (STEMI) with high troponin. He presented with acute exertional dyspnoea without chest pain. Since the initial ECG showed ST elevation anteroseptal (V1–V4) with concomitant deep Q waves, a delayed STEMI with probable left ventricular aneurysm was the working diagnosis and was treated accordingly. Nevertheless, his coronary angiography was normal and it was then that PE was suspected. D-dimer was found to be elevated and CT pulmonary angiography confirmed bilateral PE with a large thrombus within the right main pulmonary artery. The patient made good clinical recovery and his ST elevation resolved with anticoagulation. The source was found to be a deep vein thrombosis in his right leg. The treatment was not compromised by the delayed diagnosis as he received timely anticoagulation as part of STEMI management.